Implementation of Cilegon City Local Government Policy on Regional Honorary Paid for Madrasah Teachers - Eti Kurniawati; Asep Koswara; Reni Suwenti (International Journal of Nusantara Islam, 2026)
This study aims to examine the implementation of the Cilegon City Government regulation on the provision of regional allowances for madrasah educators, focusing on the supporting and inhibiting factors in its implementation, as well as its impact on teacher welfare and performance. This study uses a descriptive qualitative approach, involving sources from the Education Office, the Ministry of Religious Affairs Office, madrasah leaders, and teachers receiving regional allowances. Data were collected through in-depth interviews, observations, and review of related documents, then analyzed using the Miles and Huberman interactive model. The results show that the implementation of the regional allowance policy for madrasah teachers in Cilegon City is effective with recipient coverage reaching 92.9% of the total madrasah teachers. The main supporting factors include the political commitment of the regional head, the availability of an adequate budget of Rp 2.4 billion per year, good inter-agency coordination, and support from education stakeholders. Conversely, inhibiting factors include administrative and teacher data issues, delays in disbursement, limited coverage and amount of honorariums, and lack of socialization. This policy has a positive impact on teacher economic welfare, increases motivation and job satisfaction, and influences the quality of planning, implementation, and evaluation of learning, while encouraging teacher professional development. This study recommends the development of an integrated personnel information system, acceleration of the disbursement process, increasing the amount of honorariums and the scope of recipients, and intensifying program socialization so that policy implementation is more optimal and sustainable.